Pre-earthquake national patterns of preschool child undernutrition and household food insecurity in Nepal in 2013 and 2014. - Shrestha, Sudeep.; Thorne-Lyman, Andrew L.; Manohar, Swetha.; Shrestha, Binod.; Neupane, Sumanta.; Rajbhandary, Ruchita.; Shrestha, Raman.; Klemm, Rolf D.W.; Nonyane, Bareng A.S.; Adhikari, Ramesh K.; Webb, Patrick.; West, Keith P. (Tufts University. Tisch Library., 2018)
Abstract: Preschool undernutrition remains a burden in Nepal. This paper reports results of surveys in 2013 and 2014, examining patterns of child nutritional status across the country, associations with household food insecurity and antecedent comparative national data for subsequent evaluations of nutritional status following the earthquake in Nepal in 2015.; Keywords: Nepal, Nutrition, food security, nutrition access, economics, policy, indicators.; Participating organizations: Johns Hopkins University Bloomberg School of Public Health, Nutrition Innovation Lab, Harvard T.H. Chan School of Public Health, Helen Keller International, Kathmandu Medical College, Friedman School of Nutrition Science and Policy, Tufts University, Asia Pac J Clin Nutr.; NIL publications.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy